Speech etiquette and communicative taboos in uzbek and german cultures: a comparative pragmalinguistic analysis - Ziyaeva, Sevara Anvarovna (The Lingua Spectrum, 2026)
Cross-cultural interaction between representatives of the Uzbek and German linguocultures involves communicative risks arising from discrepancies in etiquette norms and systems of verbal restrictions. Despite the growing volume of Uzbek-German contacts in education, economics, and diplomacy, no systematic comparative description of communicative taboos in this language pair has been undertaken to date. The scientific novelty of this study lies in identifying and typologising zones of communicative taboos and etiquette mismatches in the Uzbek-German pairing, drawing on Brown and Levinson’s model of positive and negative politeness and Hofstede’s cultural dimensions framework. The aim of this research is to determine universal and culture-specific characteristics of speech etiquette and communicative prohibitions in these linguocultures. The study employs comparative pragmalinguistic analysis supplemented by discourse analysis and survey methods. The data comprise etiquette formulae extracted from textbooks, literary texts, and a questionnaire administered to 80 respondents (40 native Uzbek speakers and 40 native German speakers). Findings reveal that of the twelve identified categories of communicative taboos, complete convergence occurs in only three categories (taboos on discussing income, severe illness, and death), whereas nine categories demonstrate significant divergence. Uzbek communicative culture is characterised by a pronounced dominance of indirectness strategies and hierarchical respect, while German culture favours directness strategies and negative politeness. These findings carry practical implications for the development of intercultural communication courses and may be applied in training translators and specialists in international cooperation.